Abdelrazik v. Minister of Foreign Affairs and Attorney-General of Canada. (2014) - Unknown
Abstract : 377 Human rights — Right to enter country of nationality — Positive obligation on States to issue passports to nationals for repatriation — Intersection of United Nations Security Council resolutions with domestic human rights legislation — Standard of fairness to be observed by Minister of Foreign Affairs in refusing passports to Canadian nationals — Section 6(1) of Canadian Charter of Rights and Freedoms International organizations — United Nations — United Nations Security Council — Committee established pursuant to resolutions 1267 (1999) and 1989 (2011) — Al-Qaida Sanctions List — Asset freeze and travel ban — Proper interpretation of travel ban — Whether travel ban preventing repatriation Relationship of international law and municipal law — United Nations Security Council resolutions — 1267 Committee — Al-Qaida Sanctions List — Travel ban — Proper interpretation — Whether preventing repatriation — Constitutional provisions — Interpretation — Canadian Charter of Rights and Freedoms, Section 6(1) — Canadian Passport Order, Section 10.1 — National security as justification for breach of human rights — Judicial review — Remedy Terrorism — United Nations — Security Council Committee — Resolution 1267 (1999) — Sanctions — Al-Qaida Sanctions List — Asset freeze and travel ban — Proper interpretation of travel ban — Whether travel ban preventing repatriation to Canada — Section 6(1) of Canadian Charter of Rights and Freedoms — The law of Canada